Sex-Specific Differences in Rodents Following a Single Primary Blast Exposure: Focus on the Monoamine and Galanin Systems - Kawa, Lizan; Arborelius, Ulf P.; Hökfelt, Tomas; Risling, Mårten (Frontiers in Neurology, 2020)
Most blast-induced traumatic brain injuries (bTBI) are mild in severity and culpable for the lingering and persistent neuropsychological complaints in affected individuals. There is evidence that the prevalence of symptoms post-exposure may be sex-specific. Our laboratory has focused on changes in the monoamine and the neuropeptide, galanin, systems in male rodents following primary bTBI. In this study we aimed to replicate these findings in female rodents. Brainstem sections from the locus coeruleus (LC) and dorsal raphe nuclei (DRN) were processed for in situ hybridisation at 1 and 7 days post-bTBI. We investigated changes in the transcripts for tyrosine hydroxylase (TH), tryptophan hydroxylase two (TPH2), and galanin. Like in males, we found a transient increase in TH transcript levels bilaterally in the female LC. Changes in TPH2 mRNA were more pronounced and extensive in the DRN of females compared to males. Galanin mRNA was increased bilaterally in the LC and DRN, although this increase was not apparent until day 7 in the LC. Serum analysis revealed an increase in corticosterone, but only in exposed females. These changes occurred without any visible signs of white matter injury, cell death, or blood brain barrier breakdown. Taken together, in the apparent absence of visible structural damage to the brain, the monoamine and galanin systems, two key players in emotional regulation, are activated deferentially in males and females following primary blast exposure. These similarities and differences should be considered when developing and evaluating diagnostic and therapeutic interventions for bTBI.